Substandard, falsified and unregistered medicines in Latin America, 2017-2018 - Robin Rojas-Cortés (Pan American Health Organization, 2020)
Objective. To assess all the incidents of substandard, falsified and unregistered medicines in 2017 and 2018 in Latin America, determining the types of products affected, stages of the supply chain in which incidents were detected, quality deviations identified in tested samples, and regulatory measures taken by authorities. Methods. A comprehensive search of the websites of the Latin American national regulatory authorities was conducted, identifying all eligible incidents during 2017-2018. Standardized values were collected from each incident for pre-determined variables: country, year, type of incident, therapeutic group, supply chain, regulatory measures and laboratory data. Results. A total of 596 incidents in 13 countries were included (236 substandard, 239 falsified, 116 unregistered and 5 stolen). The therapeutic categories with the highest incidents were: anti-infectives, medicines for pain/palliative care, hormones/contraceptives, medicines for the respiratory tract, and medicines for mental/ behavioural disorders. The most common places where incidents were detected were commercial establishment, pharmacies, health services and manufacturers. The most recurrent quality deviations were failure in parameters (appearance or physicochemical), incorrect labelling, different quantity of active pharmaceutical ingredient, presence of unknown particles, and microbiological contamination. The most frequent regulatory measures identified were alerts, withdrawals, seizures, and prohibition of marketing/distribution/use. Conclusions. In Latin America, substandard, falsified and unregistered medicines persist as a highly prevalent problem. An advanced degree of regulatory development in countries is associated with higher incident detection/reporting rates and a more comprehensive set of measures. The pharmaceutical supply chain is more vulnerable in its final node. Quality deviations identified in tested samples pose serious risks to public health.